Petrodessus conatus sp. n., a new genus and species of Bidessini from hygropetric habitats in tropical Australia (Coleoptera: Dytiscidae: Hydroporinae) - Miller, Kelly B. (Zootaxa, 2012)
Petrodessus conatus sp. n., new genus and species, is described from hygropetric habitats in northeastern Australia. Thegenus is similar to Uvarus Guignot, 1939 or Microdessus Young, 1967 in lacking a transverse occipital line, a transversecarina on elytral epipleuron at the humeral angle and having both basal elytral and pronotal striae. The genus differs fromthese in having the anterior margin of the clypeus distinctly modified, flattened and anteriorly produced. This characterstate is somewhat more like that in Clypeodytes Régimbart, 1894, Leiodytes Guignot, 1936, Neoclypeodytes Young, 1967,but Petrodessus n. gen. differs from these in lacking a transverse occipital line and having the basal elytral and pronotal striae distinctly and strongly impressed. This is the first hygropetric diving beetle described from Australia.